1997
DOI: 10.1023/a:1008276022759
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract.We investigate the motion, near the equilibrium configurations, of an initially spinless rigid body subject to an external tidal field. Two cases are considered: when the center of mass of the body is at rest at the equilibrium point of the field generated by a generic mass distribution, and when it is placed on a circular orbit subject to a spherically symmetric potential. A complete analysis of the equilibrium configurations is carried out for both cases. First, we derive the conditions for the stab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The detection of this alignment from real data has been reported by many teams (Sastry 1968;Austin & Peach 1974;Dressler 1978;Carter & Metcalfe 1980;Binggeli 1982;Brainerd 2005;Yang et al 2006;Azzaro et al 2007;Wang et al 2008;Siverd et al 2009;Niederste-Ostholt et al 2010), though non-detections of this alignment were also reported (Tucker & Peterson 1988;Ulmer et al 1989). For the satellite alignment, tidal torque is thought to play a major role in its formation (Ciotti & Dutta 1994;Ciotti & Giampieri 1998;Kuhlen et al 2007;Pereira et al 2008;Faltenbacher et al 2008;Pereira & Bryan 2010). Its detection based on SDSS data has been reported by Pereira & Kuhn (2005), Agustsson &Brainerd (2006), andFaltenbacher et al (2007), while non-detections of this alignment are also reported based on data from both the 2dF Galaxy Redshift Survey (2dFGRS; Colless et al 2001;Bernstein & Norberg 2002) and SDSS (Siverd et al 2009).…”
Section: Introductionmentioning
confidence: 80%
“…The detection of this alignment from real data has been reported by many teams (Sastry 1968;Austin & Peach 1974;Dressler 1978;Carter & Metcalfe 1980;Binggeli 1982;Brainerd 2005;Yang et al 2006;Azzaro et al 2007;Wang et al 2008;Siverd et al 2009;Niederste-Ostholt et al 2010), though non-detections of this alignment were also reported (Tucker & Peterson 1988;Ulmer et al 1989). For the satellite alignment, tidal torque is thought to play a major role in its formation (Ciotti & Dutta 1994;Ciotti & Giampieri 1998;Kuhlen et al 2007;Pereira et al 2008;Faltenbacher et al 2008;Pereira & Bryan 2010). Its detection based on SDSS data has been reported by Pereira & Kuhn (2005), Agustsson &Brainerd (2006), andFaltenbacher et al (2007), while non-detections of this alignment are also reported based on data from both the 2dF Galaxy Redshift Survey (2dFGRS; Colless et al 2001;Bernstein & Norberg 2002) and SDSS (Siverd et al 2009).…”
Section: Introductionmentioning
confidence: 80%
“…It is commonly believed that tidal torques are responsible for this radial alignment (e.g. Ciotti & Dutta 1994; Ciotti & Giampieri 1998; Pereira et al 2008), as tidal forces on these relatively small scales (≲1 Mpc ) are sufficiently strong to affect halo shapes on short time‐scales.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we consider the (rigid) oscillations of elliptical galaxies (a similar analysis has been carried out in Ciotti & Giampieri 1997) and the precession of spiral galaxies. We show below that internal dynamics is much faster than rigidbody dynamics, thus confirming the results of Ciotti & Dutta (1994) for elliptical galaxies.…”
Section: Appendix A: Rigid-body Approximationmentioning
confidence: 99%